REFORMASI APARATUR NEGARA UNTUK MELAKSANAKAN TATA KELOLA PEMERINTAHAN YANG BAIK DAN BENAR (GOOD GOVERNANCE) - Saragih, Jopinus (MAJALAH ILMIAH WIDYA, 2012)
It is necessary to reform of the state apparatus in order to create a system that enable the administration to implement thegood governance, should be comprehensive which regarding the determination of the basic rules of the states goverment systemin accordance with the progress of the nation of Indonesia. The purpose of this paper is to discuss what the goverment should bepursued improving the ability of the goverment bureaucracy, especially in the civil service system, decentralization of goverment andefforts to combat corruption. The method used literature study. It can be concluded that the success of the performance of goodgovernance both at central and regional levels will be determined by the quality and quantity of resources apparatus.